An Analysis of Business Strategy of A B2B Small Medium Enterprises in Tasikmalaya - Handiri, Inka; Nurfitriya, Mira; Rachmani, Nizza Nadya (Universitas Pendidikan Indonesia, 2024)
Business competition in the textile and clothing industry is getting tighter. Many competitors cause companies in that field to experience a decrease in sales. This study intends to formulate a business strategy using the SWOT analysis tool so that companies know what must be maintained and improved in increasing sales to excel in business competition. This study uses a qualitative method with a case study approach. The findings from the study used the QSPM matrix analysis. There are 3 priorities for the formulation of a new strategy, namely a field research strategy, a strategy for evaluating and analysing market trends, and increasing digital marketing. The implications obtained by the company are increasing market demand, developing markets, and being able to compete with competitors.